Primary Aldosteronism: Current trends and challenges to the diagnosis (Journal of Association of Clinical Endocrinologist and Diabetologist of Bangladesh, 2025)
Primary aldosteronism (PA) is the autonomous secretion of aldosterone from the adrenals causing excess salt and water retention from the kidneys. It is now a well-established fact that PA is a widely prevalent disorder affecting one in ten hypertensive patients with early and inappropriate target organ damage. It has got excellent response to targeted therapy namely the mineralocorticoid receptor antagonists (MRAs) or surgery for aldosterone producing adenoma (APA) whereas first-line anti-hypertensives medications are mostly ineffective. However the diagnosis is often missed or delayed because of the absence of typical clinical phenotype or the use of hypokalemia as an obligatory screening pre-requisite. While hypokalaemia was historically considered as a hallmark of PA, near about 40% patients are normokalaemic, leading to missed diagnoses. The current diagnostic pathway is challenging for the physician requiring meticulous patient selection and preparation followed by adoption of the screening and the confirmatory biochemical testing that best corroborate the local expertise. Adrenal venous sampling (AVS), thought to be gold standard procedure for subtype differentiation, is limited by its cost, availability, technical demand and high inter-center variability. It is imperative to create awareness regarding this commonplace disease and establish a center-specific, simplified, convenient and cost-effective diagnostic protocol.J Assoc Clin Endocrinol Diabetol Bangladesh, January 2025;4(1): 21-30